Neutral current neutrino-nucleon interaction and the Δ(1232) - Mariano, Alejandro Edgardo (2010)
Neutrino-induced one-pion production off nucleons and nuclei in the intermediate energy region, is a source of relevant data on hadronic structure. On the other hand, a proper understanding of these processes is very important in the analysis of neutrino oscillation experiments, where the weak production of pions is the main background. Then, it is important develop a consistent model to have under control the charged (CC) and neutral current (NC) pion production cross sections. Working within an isobar model previously developed to describe elastic and radiative pion-nucleon cross sections and pion photoproduction reactions, using the axial form factors (FF) already obtained from the study of the CC neutrino-nucleon currents, we analyze its predictive power in the NC current production case.